2021
DOI: 10.1021/jasms.1c00274
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Higher Order Structure and Dynamic Investigation Method of Proteins in Solution Using an Enzymatic Reactor Coupled to Electrospray High-Resolution Mass Spectrometry Detection

Abstract: For decades, structural analysis of proteins have received considerable attention, from their sequencing to the determination of their 3D structures either in the free state (e.g., no host–guest system, apoproteins) or (non)­covalently bound complexes. The elucidation of the 3D structures and the mapping of intra- and intermolecular interactions are valuable sources of information to understand the physicochemical properties of such systems. X-ray crystallography and nuclear magnetic resonance are methods of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The online enzymatic reactor used in this study was previously detailed elsewhere. 16 In summary, the designed enzymatic digestion reactor comprised two pumps: a thermostatic syringe containing the targeted protein and the enzyme (flux of 4 μL min −1 ) and a second syringe containing 10% acetonitrile + formic acid 0.2% (v/v) (flux of 4 μL min −1 ) used to quench the enzymatic digestion reaction in the mixing chamber prior to the MS analysis (see Figure S2). The enzyme was introduced to the sample just before injection to monitor the enzymatic digestion of the model proteins over time.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The online enzymatic reactor used in this study was previously detailed elsewhere. 16 In summary, the designed enzymatic digestion reactor comprised two pumps: a thermostatic syringe containing the targeted protein and the enzyme (flux of 4 μL min −1 ) and a second syringe containing 10% acetonitrile + formic acid 0.2% (v/v) (flux of 4 μL min −1 ) used to quench the enzymatic digestion reaction in the mixing chamber prior to the MS analysis (see Figure S2). The enzyme was introduced to the sample just before injection to monitor the enzymatic digestion of the model proteins over time.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In our previous study, we demonstrated how the secondary structure of proteins and peptides influences the initial apparition rate 16 and time of appearance of peptides generated by a protease. The initial apparition rate of released peptides was found to be directly dependent on the protein's state (folded or denatured) and the cleavage site's location on structural domains (α-helix/β-sheet) or flexible domains.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation